2009
DOI: 10.1111/j.1365-2672.2008.03993.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to controlSalmonella entericaby modern biophotonic technology: photosensitization

Abstract: Aims:  Salmonellosis is one of the most common foodborne diseases in the world. The aim of this study was to evaluate the antibacterial efficiency of 5‐aminolevulinic acid (ALA) based photosensitization against one of food pathogens Salmonella enterica. Methods and Results:  Salmonella enterica was incubated with ALA (7·5 mmol l−1) for 1–4 h and afterwards illuminated with visible light. The light source used for illumination of S. enterica emitted light λ = 400 nm with energy density 20 mW cm−2. The illuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 16 publications
0
40
1
Order By: Relevance
“…Increasing the concentration to 7.5 mM and the incubation time to 30 min caused 2.7 log decrease on spores adhered to packaging [55]. An efficient inactivation (6 log) of Salmonella enterica serovar Typhimurium resistant to tetracycline (10 7 CFU mL −1 ) was achieved after 60 min incubation with 7.5 mM of 5-ALA and 20 min irradiation (24 J cm −2 ) [54]. In the case of L. monocytogenes, in vitro tests showed that cells were inactivated by 4 logs with 7.5 mM 5-ALA, incubated 120 min and irradiated 20 min.…”
Section: Elimination Of Food-borne Pathogensmentioning
confidence: 88%
See 3 more Smart Citations
“…Increasing the concentration to 7.5 mM and the incubation time to 30 min caused 2.7 log decrease on spores adhered to packaging [55]. An efficient inactivation (6 log) of Salmonella enterica serovar Typhimurium resistant to tetracycline (10 7 CFU mL −1 ) was achieved after 60 min incubation with 7.5 mM of 5-ALA and 20 min irradiation (24 J cm −2 ) [54]. In the case of L. monocytogenes, in vitro tests showed that cells were inactivated by 4 logs with 7.5 mM 5-ALA, incubated 120 min and irradiated 20 min.…”
Section: Elimination Of Food-borne Pathogensmentioning
confidence: 88%
“…The different effectiveness between photosensitization of biofilms and the cells adhered to the surface of packaging material was explained by the polysaccharide matrix of biofilms acting as a diffusion barrier for PS and reducing its accumulation inside bacteria [53]. The fluorescence intensity analysis of endogenous PS in these three microorganisms revealed that B. cereus produces endogenous porphyrins 10 times more efficiently than L. monocytogenes or S. enterica [54,100], explaining its higher susceptibility to 5-ALA-based photosensitization compared to the other two bacteria.…”
Section: Elimination Of Food-borne Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar approaches using preincubation with ALA to achieve photosensitization-based inactivation has also been used to achieve enhanced inactivation of other bacteria including Bacillus cereus (30) and S. enterica (31).…”
Section: Discussionmentioning
confidence: 99%